Zasoby wodne w Republice Kirgiskiej i państwach regionu Azji Centralnej jako jeden z aspektów geopolityki - Fiedler, Radosław; Subanov, Mirlan (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper analyzes the concept of water resources as one of the aspects of geopolitics. It addresses the contemporary state of water relations, as well as their evolution in various periods of Central Asia’s history. It also presents the disputes concerning the joint management of cross-border water resources by Central Asia’s republics. Domestic and international regulations are examined alongside the unilateral policy of Central Asia’s states, which may result in conflicts over water resources.
Water resources in the Kyrgyz Republic and the states of Central Asia as a geopolitical aspect